THE IMPACT OF SURAH AR-RAHMAN RECITATION ON SHORT-TERM MEMORY IN MEDICAL STUDENTS: A QUASI-EXPERIMENTAL STUDY - Fakhri, Sarah Humayra; Syauqi, Ahmad; Shafira, Nyimas Natasha Ayu; Fakhri, Ayushia Generosa (MNJ (Malang Neurology Journal), 2026)
Background: Short-term memory (STM) is crucial for learning and academic success, particularly in demanding fields, such as medical education. Recent studies have suggested that auditory spiritual interventions, such as listening to Qur’anic recitation, may positively influence cognitive function. However, the evidence specific to Surah Ar-Rahman and its impact on STM among medical students remains limited. Objective: To investigate the impact of listening to Surah Ar-Rahman on the short-term memory performance of medical students. Methods: This quasi-experimental, pre- and post-test controlled study was conducted with 46 second-semester medical students from the Faculty of Medicine and Health Sciences, University of Jambi, Indonesia. Participants were randomly assigned to either an intervention group (listening to Surah Ar-Rahman for 12 min) or a control group (resting quietly for 12 min). Short-term memory was assessed using the digit span test before and after the intervention. Data were analyzed using paired and independent sample t-tests, and effect sizes were calculated using Cohen’s d-. Results: The intervention group showed a significant increase in digit span scores post-intervention (mean difference = 1.48, p < 0.001, Cohen’s d = 0.87), indicating a large effect. No significant changes were observed in the control group. Post-test scores between the groups were significantly different (p = 0.011). Conclusion: Listening to Surah Ar-Rahman had a substantial positive effect on medical students’ short-term memory. This non-pharmacological intervention may be a valuable adjunct to cognitive optimization strategies in medical education.